2002
DOI: 10.1002/micr.10055
|View full text |Cite
|
Sign up to set email alerts
|

Effect of long‐term application of epinephrine on rat skin vasculature: Experimental study

Abstract: As a potent vasoconstrictor, epinephrine is used ubiquitously in plastic surgery. It is typically delivered subcutaneously in very low concentrations over a brief time interval. We are aware of no reports describing the long-term release of epinephrine as an independent agent to the soft tissues for the purpose of causing prolonged local vasoconstriction. This study was designed to address two goals: first, to investigate the effect of long-term local release of epinephrine from a drug delivery system on rat a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 18 publications
(10 reference statements)
0
8
0
Order By: Relevance
“…4,5 Epinephrine is used extensively in the practice of plastic surgery, principally for its potent vasoconstrictor effect on skin and subcutaneous tissue. It is applied locally for a short duration (i.e., 1 to 2 hours).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…4,5 Epinephrine is used extensively in the practice of plastic surgery, principally for its potent vasoconstrictor effect on skin and subcutaneous tissue. It is applied locally for a short duration (i.e., 1 to 2 hours).…”
Section: Discussionmentioning
confidence: 99%
“…Until recently, no data were available for the long-term administration of epinephrine. 4,5 However, recent studies have demonstrated that epinephrine administered by protracted depot *These values were recorded on certain days along with mean Ϯ SD at the different intervals. Laser Doppler flowmeter measurements in tissue blood flow (in milliliters per minute per 100 g of tissue) revealed a significant difference between groups (p Ͻ 0.05) (see Fig.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations